Match-Fixing Causing Harm to Athletes on a COVID-19-Influenced Gambling Market: A Call for Research During the Pandemic and Beyond - Håkansson, A; Jönsson, C; Kenttä, G (Frontiers in Psychology, 2021)
Match-fixing, although not a new problem, has received growing attention during the COVID-19 pandemic, which has been reported in the media to have increased the risk of match-fixing events. Gambling is a well-documented addictive behavior, and gambling-related fraud, match-fixing, is a challenge to the world of sports. Most research on match-fixing has a judicial or institutional perspective, and few studies focus on its individual consequences. Nevertheless, athletes may be at particular risk of mental health consequences from the exposure to or involvement in match-fixing. The COVID-19 crisis puts a spotlight on match-fixing, as the world of competitive sports shut down or changed substantially due to pandemic-related restrictions. We call for research addressing individual mental health and psycho-social correlates of match-fixing, and their integration into research addressing problem gambling, related to the pandemic and beyond.